Solution of the Differential Equations Governing the Equilibrium of a Skew-Curved Beam - Panayotounakos, D.E.; Theocaris, P.S. (Engineering Transactions, 1980)
The present paper deals with the closed form solution of the differential equations, with variable coefficients, governing the equilibrium of a skew or planar-curved beam. This problem is associated with a system or twelve coupled linear differential equations of first order, the closed form solution of which was achieved through tow analytical methods.